Doxycycline hyclate: a review of properties, applications and analytical methods - Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes (My University, 2012)
The doxycycline hyclate is a broad-spectrum antibiotic oxytetracycline synthetic derivative used in several countries. It has been used to treat infectious diseases and as an additive in animal nutrition to facilitate growth. This drug is part of the list of medicines to the SUS (Unified Health System), a model of health care in Brazil, and it is free delivery in the public with a medical prescription. Thus, it is extremely important quality control of this medicine to be able to ensure their effectiveness and safety. Several existing analytical techniques, which offer flexible and broad-based methods of analysis and in some cases detection, have been discussed in this manuscript, focusing on bioanalytical and pharmaceutical quality control applications. This review will examine the published analytical methods reported for determination of doxycycline hyclate, discussing (a) separation methods such as thin layer chromatography and high performance liquid chromatography (HPLC) and (b) others such as, spectrophotometry and microbiological assay, from which it can be seen that HPLC methods have been used most extensively.
Keywords: Doxycycline hyclate; Analytical methods; Quality control